Random sequential adsorption of straight rigid rods on a simple cubic lattice - García, Guillermo Daniel (2015)
Random sequential adsorption of straight rigid rods of length k (k-mers) on a simple cubic lattice has been studied by numerical simulations and finite-size scaling analysis. The k-mers were irreversibly and isotropically deposited into the lattice. The calculations were performed by using a new theoretical scheme, whose accuracy was verified by comparison with rigorous analytical data. The results, obtained for k ranging from 2 to 64, revealed that (i) the jamming coverage for dimers (k=2) is θj=0.918388(16). Our result corrects the previously reported value of θj=0.799(2) (Tarasevich and Cherkasova, 2007); (ii) θj exhibits a decreasing function when it is plotted in terms of the k-mer size, being θj(∞)=0.4045(19) the value of the limit coverage for large k’s; and (iii) the ratio between percolation threshold and jamming coverage shows a non-universal behavior, monotonically decreasing to zero with increasing k.